RAGAM METODE TAKHRIJ HADIS: DARI ERA TRADISIONAL HINGGA DIGITAL - Althaf Husein Muzakky; Muhammad Mundzir (IAIN Syekh Nurjati Cirebon, 2022)
The need to find original sources of Hadith texts is an urgent part of Hadith studies. This study briefly discusses the various methods of takhrij hadith from traditional and modern. Through qualitative research, this paper concludes that there are five methods of takhrij Hadith, namely the first word, vocabulary, the first narrator, thematic hadith, and hadith quality. On the other hand, there are shofwere Jawam Alkalim and Mausu'ah Hadith which can be accessed on computers, gadgets, both offline and online.